Lessons from Uganda on strategies to fight poverty - Mackinnon, John (Policy research working paper, 2000)
Lessons from Uganda on preparing a national strategy for poverty reduction, with stakeholders participating. Uganda's experience contributed substantially to the design of the Poverty Reduction Strategy Papers